PID control of FOPDT plants with dominant dead time based on the modulus optimum criterion - Cvejn, Jan (DE GRUYTER OPEN LTD, 2016)
The modulus optimum (MO) criterion can be used for analytical design of the PID controller for linear systems with dominant dead time. However, although the method usually gives fast and non-oscillating closed-loop responses, in the case of large dead time the stability margin gets reduced and even non-stable behavior can be observed. In this case a correction of the settings is needed to preserve the stability margin. We describe and compare two methods of design of the PID controller based on the MO criterion that for the stable first-order systems with dead time preserve the stability margin, trying to keep maximum of the performance of the original MO settings.
PID řízení systémů FOPDT s dominantním dopravním zpožděním na základě metody optimálního modulu
Keywords: PID controller; process control; dead time; modulus optimum; magnitude optimum; PID regulátor; řízení procesů; dopravní zpoždění; optimální modul